Pengaruh Pesan Kampanye Public Relations #RespectMyBody Terhadap Brand Awareness Bodycare Somethinc - Diaz Mega Reanata; Winda Dwi Astuti Zebua (Jurnal Mahasiswa Kreatif, 2024)
The problem of self-love is still a social issue in society. Somethinc complements management company by creating a #RespectMyBody campaign as a form of concern for that issue. Through this campaign, Somethinc invites people to take care of their bodies as a form of appreciation and self-love. Through the #RespectMyBody campaign, Somethinc released a new product in the form of bodycare. Therefore, it is necessary to rebuild brand awareness. The purpose of this research is to find out how much influence the message of the #RespectMyBody public relations campaign has on bodycare Something brand awareness. The theory used in this research is Persuasive Public Relations Campaign Messages (Message Structure, Message Content, Framing, Language, Emotional Attraction). As well as Brand Awareness (Brand Recall, Brand Recognition, Purchase Decision, Consumption). This study uses a quantitative approach and survey method by distributing questionnaires to 98 samples determined using Taro Yamane calculations with probability sampling techniques. The measurement results for the X variable were 3.66 and the Y variable was 3.64. Meanwhile, the influence is 62.3%, while the remainder is 37.7%. By proving that there is an influence, the results of the hypothesis test obtained tcount 20.326 > ttable 1.661, then H0 is rejected and H1 is accepted, which means the regression coefficient is significant, namely that there is an influence between the #RespectMyBody public relations campaign message on Somethinc bodycare brand awareness.